Novel aspects of pathogenicity of Aliivibrio salmonicida - Kashulin, Alexander (UiT Norges arktiske universitet, 2014)
List of papers: Paper I: Kashulin, A., Sørum, H.: “A novel in vivo model for rapid evaluation of Aliivibrio salmonicida infectivity in Atlantic salmon”. Also available in Aquaculture 2014, 420-421:112-118. Paper II: Kashulin, A., Sørum, H.: «Early bacteremia in Atlantic salmon (Salmo salar) and rainbow trout (Oncorhynchus mykiss) during immersion challenge with Aliivibrio (Vibrio) salmonicida”. (Manuscript). Paper III: Kashulin, A., Sørum, H., Hjerde, E., Willassen, N. P.: «IS elements in Aliivibrio salmonicida LFI1238: Occurrence, variability and impact on adaptability”. Also available in Gene 2015, 554(1):40-49. Analysis of the fish health reports annually published online by the Norwegian Veterinary Institute (data available starting from 2005), have demonstrated a good epidemiological situation with Cold Water Vibriosis (CWV) in 2005-2010. During this 5 year period only 4 cases were detected in Norway. Starting from 2011 the situation began to change and only during 2011, 5 cases of CWV have been detected in Norway. In 2012 outbreaks of CWV occurred at 21 farms affecting vaccinated Atlantic salmon. In 2013, 13 outbreaks occurred. Regarded as a disease fully controlled by vaccination until 2011, CWV again became a considerable disease in the annual fish health reports. The motivation for this study originated from the hypothetical impact of mobile genetic elements on bacterial adaptation to pathogenicity in other host species than Atlantic salmon and the recent apparent inability of vaccination to provide acceptable protection against CWV. Analysis of nearly 90 research papers dedicated to CWC in 1975-2014 demonstrated a lack of important data on the early dynamics of the disease as well as a lack of clear information on the portal of CWV infection. The aim of the current project was to fill in the gaps in the knowledge on early dynamics and portal of infection for Cold Water Vibriosis (CWV) as well as to characterize mobile genetic elements potentially driving adaptation of Aliivibrio salmonicida to ...